Authentic Leadership on Psychological Capital of ASN Employees with Life-Work Balance as an Intervening - Idra Maya; Adi Rahmat; Helwen Heri (SAINS ORGANISASI, 2022)
This study aims to see how the influence of Authentic Leadership on the Psychological Capital of ASN Employees with Life-work Balance as an Intervening. This type of research is explanatory research. The population is ASN employees of the Rokan Hulu District Health Office, totaling 65 people. Data analysis in this study used SEM-PLS. Based on the data processing, it was found that there was a significant effect of Authentic Leadership on Psychological Capital, there was also a significant effect of authentic leadership on work-life balance, the variable of work-life balance on psychological capital, and work-life balance was stated to be able to mediate the influence of Authentic leadership on Psychological Capital in ASN employee of the Rokan Hulu Health Service. Based on the results of research, social support and organizational citizenship behavior have an influence on psychological capital, so that all elements of the Rokan Hulu District Health Office should improve work life balance indicators and authentic leadership.